Efficacy, efficiency and safety of a cardiac telerehabilitation programme using wearable sensors in patients with coronary heart disease: the TELEWEAR-CR study protocol. Issue 6 (23rd June 2022) - Antoniou, Varsamo; Xanthopoulos, Andrew; Giamouzis, Gregory; Davos, Constantinos; Batalik, Ladislav; Stavrou, Vasileios; Gourgoulianis, Konstantinos I; Kapreli, Eleni; Skoularigis, John; Pepera, Garyfallia
Abstract : Introduction: Exercise-based cardiac rehabilitation (CR) is a beneficial tool for the secondary prevention of cardiovascular diseases with, however, low participation rates. Telerehabilitation, intergrading mobile technologies and wireless sensors may advance the cardiac patients' adherence. This study will investigate the efficacy, efficiency, safety and cost-effectiveness of a telerehabilitation programme based on objective exercise telemonitoring and evaluation of cardiorespiratory fitness. Methods and analysis: A supervised, parallel-group, single-blind randomised controlled trial will be conducted. A total of 124 patients with coronary disease will be randomised in a 1:1 ratio into two groups: intervention telerehabilitation group (TELE-CR) (n=62) and control centre-based cardiac rehabilitation group (CB-CR) (n=62). Participants will receive a 12-week exercise-based rehabilitation programme, remotely monitored for the TELE-CR group and standard supervised for the CB-CR group. All participants will perform aerobic training at 70% of their maximal heart rate, as obtained from cardiopulmonary exercise testing (CPET) for 20 min plus 20 min for strengthening and balance training, three times per week. The primary outcomes will be the assessment of cardiorespiratory fitness, expressed as peak oxygen uptake assessed by the CPET test and the 6 min walk test. Secondary outcomes will be the physical activity, the safety of the exercise intervention (number of adverse events that may occur during the exercise), the quality of life, the training adherence, the anxiety and depression levels, the nicotine dependence and cost-effectiveness. Assessments will be held at baseline, end of intervention (12 weeks) and follow-up (36 weeks). Ethics and dissemination: The study protocol has been reviewed and approved by the Ethics Committee of the University of Thessaly (1108/1-12-2021) and by the Ethics Committee of the General University Hospital of Larissa (3780/31-01-2022). The results of this study will be disseminated through manuscript publications and conference presentations. Trial registration number: NCT05019157 .